2011
DOI: 10.1371/journal.pone.0021908
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of Cathepsin D Affects the Retinal Pigment Epithelium, Impairs Swim-Bladder Ontogenesis and Causes Premature Death in Zebrafish

Abstract: The lysosomal aspartic protease Cathepsin D (CD) is ubiquitously expressed in eukaryotic organisms. CD activity is essential to accomplish the acid-dependent extensive or partial proteolysis of protein substrates within endosomal and lysosomal compartments therein delivered via endocytosis, phagocytosis or autophagocytosis. CD may also act at physiological pH on small-size substrates in the cytosol and in the extracellular milieu. Mouse and fruit fly CD knock-out models have highlighted the multi-pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 70 publications
2
38
0
Order By: Relevance
“…Nevertheless, recent advances have been made in the clinic that show promise for small molecule inhibition of BACE1 [47], yet most of these approaches still lack the specificity that an antibody approach will offer. In particular, there are clear risks associated with cathepsin-D inhibition [48][49][50], and the risks associated with BACE2 inhibition are not yet evident. Recent genetic studies have also raised the concern that complete inhibition of BACE1 itself may be deleterious [51][52][53].…”
Section: Using Anti-bace1 To Reduce Aβ Productionmentioning
confidence: 99%
“…Nevertheless, recent advances have been made in the clinic that show promise for small molecule inhibition of BACE1 [47], yet most of these approaches still lack the specificity that an antibody approach will offer. In particular, there are clear risks associated with cathepsin-D inhibition [48][49][50], and the risks associated with BACE2 inhibition are not yet evident. Recent genetic studies have also raised the concern that complete inhibition of BACE1 itself may be deleterious [51][52][53].…”
Section: Using Anti-bace1 To Reduce Aβ Productionmentioning
confidence: 99%
“…Zebrafish have also proven to be a helpful system in studying miRNA functions during developmental processes [44]. Identification and characterization of miRNAs in zebrafish have provided important information regarding the conservation of miRNA genes in vertebrates.…”
Section: Zebrafish and Micrornamentioning
confidence: 99%
“…The role of a miRNA in larvae and adult animals can be investigated by using Cre-loxP or TALEN technologies that allow stable and conditional miRNA down or overexpression in a tissue-specific manner [48]. Several vascular specific miRNAs have been identified and studied in zebrafish inter alia miR-24, miR-92, miR-126, and miR-221 [44,48]. Some of them act as anti-angiogenic factors.…”
Section: Zebrafish and Micrornamentioning
confidence: 99%
“…The pathophysiological role of CD in organ development and homoeostasis can be inferred from the phenotype of knockdown and knockout animal models, as described in mouse [1], fruitfly [2] and zebrafish [3]. One main function of CD is to degrade long-lived proteins transferred into the lysosomes via endocytosis, phagocytosis and autophagy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that zebrafish zygotes lacking CD develop to larvae that present with several phenotypic alterations, including failure of yolk absorption, reduced body length, microphthalmia and defective development of the digestive tract, the swim bladder and the retina-pigmented epithelium [3]. In this work, we focused our attention on the development of the somitic musculature in CD-knockdown zebrafish.…”
Section: Introductionmentioning
confidence: 99%